THE ESSENCE OF VILLAGE AS A CONSTITUTIONAL GOVERMENT ORGAN IN STATE MANAGEMENT SYSTEMS - Muhammad Mashuri (Jurnal Analisis Hukum, 2020)
Historically, all local communities in Indonesia have strong local wisdom which contains a spirit of sufficiency, balance and sustainability, especially in managing natural resources and people. It is philosophically clear that before governance over it existed, the Village first existed. The purpose of this research is to elaborate on the village as the basis and part of the governance arrangement afterward. A village that has an older government system should also be the spearhead in every administration of government, development and community affairs. The research used in this study is normative research using secondary data such as statutory regulations, legal theory, expert opinion, and court decisions. The approach that the writer uses is the approach of the Invitation Laws and the conceptual approach. The result of this paper is that Village autonomy and democracy which will be framed by a law on villages is not just an institutional matter, but has a deep philosophical basis. Efforts to strengthen regional autonomy and "village autonomy" are part of these ideals, as well as aiming to build a strong and perfect Indonesian imagination, which goes beyond centralism and localism. NKRI will become stronger if it is supported by the sovereignty of the people and the independence of the local people (regions and villages), namely the center that "respects" the local and the local "respects" the center. Village independence will be the foundation and strength of the Republic of Indonesia and Indonesia's imagination. If the village is forever marginal and dependent, it will become a heavy burden for the government and paralyze the foundations of the Republic of Indonesia. In the future, we need the village as a local entity that is socially powerful, politically sovereign, economically empowered and culturally dignified.